From future diets to dishes: communicating dietary shift associated with a 1.5°C scenario for Brazil, China, Sweden and the United Kingdom - Lee, Susan; Freer, Muir; Wood, Ruth; Edelenbosch, Oreane; Sharmina, Maria; Doelman, Jonathan; van Vuuren, Detlef; Wilson, Charlie (Frontiers in Sustainable Food Systems, 2023)
Introduction With the pressing need to mitigate greenhouse gas emissions, this study aims to simplify complex data from Integrated Assessment Models (IAMs). It focuses on identifying dietary shifts that align with the 1.5°C global warming limit as stipulated by the Paris Agreement. Methods The research utilises the IMAGE Integrated Assessment Model and applies the Diets, Dishes, Dish Ingredients (DDDI) communication framework. This methodology enables the visualisation of potential dietary and dish composition changes, thereby making the data more comprehensible to a broader audience. Results The study effectively translates traditional IAM outputs into accessible visualisations. These visual tools provide a nuanced understanding of a low greenhouse gas diet, extending its relevance beyond academia to include professionals in diet and nutrition. Discussion This research stands as a significant advancement in the field, lowering the barrier to understanding sustainable diets for the future. It enriches the existing dialogue on dietary change and climate goals and serves as a catalyst for further research and practical applications in diverse contexts.